Substrate delivery by the AAA+ ClpX and ClpC1 unfoldases activates the mycobacterial ClpP1P2 peptidase - Schmitz, Karl R. (2014)
Mycobacterial Clp-family proteases function via collaboration of the heteromeric ClpP1P2 peptidase with a AAA+ partner, ClpX or ClpC1. These enzymes are essential for M. tuberculosis viability and are validated antibacterial drug targets, but the requirements for assembly and regulation of functional proteolytic complexes are poorly understood. Here, we report the reconstitution of protein degradation by mycobacterial Clp proteases in vitro and describe novel features of these enzymes that distinguish them from orthologs in other bacteria. Both ClpX and ClpC1 catalyze ATP-dependent unfolding and degradation of native protein substrates in conjunction with ClpP1P2, but neither mediates protein degradation with just ClpP1 or ClpP2. ClpP1P2 alone has negligible peptidase activity, but is strongly stimulated by translocation of protein substrates into ClpP1P2 by either AAA+ partner. Interestingly, our results support a model in which both binding of a AAA+ partner and protein-substrate delivery are required to stabilize active ClpP1P2. Our model has implications for therapeutically targeting ClpP1P2 in dormant M. tuberculosis, and our reconstituted systems should facilitate identification of novel Clp protease inhibitors and activators.